A Review of Resting-State Electroencephalography Analysis in Disorders of Consciousness - Bai, Yang; Xia, Xiaoyu; Li, Xiaoli (Frontiers in Neurology, 2017)
Recently, neuroimaging technologies have been developed as important methods for assessing the brain condition of patients with disorders of consciousness (DOC). Among these technologies, resting-state electroencephalography (EEG) recording and analysis has become widely applied by clinicians due to its relatively low cost and convenience. EEG reflects the electrical activity of the underlying neurons, and it contains information regarding neuronal population oscillations, the information flow pathway and neural activity networks. Some features derived from EEG signal processing methods have been proposed to describe the electrical features of brains with DOC. The computation of these features is challenging for clinicians working to comprehend the corresponding physiological meanings and then to put them into clinical applications. This paper reviews studies which analyze spontaneous EEG of DOC, with the purpose of diagnosis, prognosis and evaluation of brain interventions. It is expected that this review will promote our understanding of the EEG characteristics in DOC.